Life experience of Malay women who underwent induced lactation in Selangor and Kuala Lumpur, Malaysia - Hassan, Shahirah Mohd (2021)
Induced lactation is breastfeeding without prior pregnancy. There is lack of studies regarding experiences of women who induced lactation. It is crucial that evidence-based information on experiences of women who induced lactation is available to health professionals and other individuals in Malaysia. This study aims to explore the experiences of women who induced lactation in Selangor and Kuala Lumpur, specifically on the perception of satisfaction, emotions, enablers and challenges in induced lactation. Informants were purposively recruited from a list of breastfeeding support groups in Selangor and Kuala Lumpur. Along the way, snowball sampling was adopted to maximize variation. Face-to-face interviews were conducted using semi-structured interview guide with consented informants that fit inclusion criteria. Informants were interviewed until saturation achieved. Interviews were audio recorded and transcribed verbatim. Qualitative data was managed and thematic analysis conducted using RQDA software. A total of 20 informants participated in the study. All informants were Malay and Muslims with age between 26 to 47 years, majority had tertiary education (80%), married (95%) and employed (70%) during the time of induced lactation. Infants were adopted by infomants between the age of one to 21 days, and majority had no newborn complications (90%). Thematic analysis findings were presented into four sections which included perception of satisfaction of women who induced lactation, emotions along the process of induced lactation, enablers to attain satisfaction in induced lactation and challenges in induced lactation. Themes raised from informants’ perception of satisfaction were the ability to experience motherhood and religious factors in facilitating the decision. Themes emerged from emotions along the process were emotions when starting induced lactation, emotions when facing challenges during induced lactation and emotions when breastmilk yield established. Themes emerged from enablers to satisfaction in induced lactation were self-compliant behaviour, self-efficacy and supportive environment. Themes emerged from challenges in induced lactation were non-compliant behaviour, personal barriers and environmental obstacles. Findings from this study proves each woman seeking to induce lactation will have a unique individual experience. Similarities in findings can be used as basic knowledge to develop induced lactation guideline but management plan should incorporate consideration for individual needs and compatibility. Managing expectations along with a sturdy support system are essentials to ensure women who induce lactation achieve satisfaction according to their personal goals. Further studies bridging knowledge gap and exploring new findings in this study should be considered.